Kajian Etnomatematika Alat Musik Gong Waning Khas Nusa Tenggara Timur - Kumoro, Timotius Sapto; Putraditama, Sebastianus Hanamas; Victory, Christian Gilly (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study discusses the ethnomathematics study of the gong instrument in the East Nusa Tenggara gong gong musical instrument. Gong Waning itself is a traditional musical instrument typical of the Sikka people, East Nusa Tenggara which existed around the 1920s. Gong Waning Musical Instruments are divided into 3 musical instruments namely gong, waning, and sa’ur. The gong itself is divided into several types, namely inan gong, child gong, udong gong, beit gong, and lepen gong. then waning which consists of waning inan, and waning child. Sa’ur is a musical instrument made of bamboo strips about 1.5 m long. This study uses a qualitative research method by conducting interviews with informants who are gong players on the gong waning musical instrument. later in this research, we can find out that in the gong musical instrument in the East Nusa Tenggara gong gong musical instrument, we can examine the ethnomathematics contained in each of the gong gong musical arts.